Ireland in the European eye (ROYAL IRISH ACADEMY, 2019)
"A comprehensive survey of Ireland's place in Europe, providing a detailed narrative of a cultural relationship that began with Irish missionaries bringing Christianity and learning to the continent. How have Ireland and her people and culture been perceived and represented in Europe? Twenty-two internationally renowned experts address this question through contributions on film, music, art, architecture, media, literature and European Studies"--Publisher's website